Earning Management Analysis before and after Implementation of International Financial Reporting Standards (IFRS): Empirical Study of Automotive and Components Companies Registered on the IDX - Anis Purwanti; I Wayan Wisnu Utama (JASF: Journal of Accounting and Strategic Finance, 2018)
The issue of the application of IFRS as a standard can encourage a decrease in the level of earnings management in a company, so that the application of IFRS in financial statements has the purpose of providing reports that are faithful in nature so that the report users are reliable. The purpose of this study is to show a comparison of earnings management practices that occurred before and after the implementation of International Financial Reporting Standards (IFRS) in Automotive and Component companies registered in the Indonesia Stock Exchange (IDX) for the period of 2009-2014. The data used in this study are secondary data in the form of company’s financial statements. The variables in this study are earnings management before and after IFRS implementation. The sampling method in this study was purposive sampling with a sample of 12 automotive and component companies on the Indonesia Stock Exchange. Discretionary accruals of Modified Jones Model is used to measure the earnings management. The analytical method used for hypothesis testing is Paired Sample T-test, a different test for two paired samples. The results of this study indicate that earnings management in the period after IFRS convergence was different than earnings management in the period before IFRS convergence in Automotive and Component companies. However, IFRS convergence has not guaranteed a decline in earnings management practices in Automotive and Component companies.